Presence of NGAL/MMP-9 complexes in human abdominal aortic aneurysms - Folkesson, Maggie; Kazil, Monsur; Zhu, Chaoyong; Silveira, Angela; Hemdahl, Anne-Louise; Hamsten, Anders; Hedin, Ulf; Swedenborg, Jesper; Eriksson, Per (Thrombosis and Haemostasis, 2007)
It has been suggested that the intraluminal thrombus of abdominal aortic aneurysms (AAAs) predisposes for AAA enlargement and rupture.The growth of theAAA is dependent on proteolytic degradation of elastin. Here, we analysed whether the neutrophil gelatinase-associated lipocalin (NGAL) is expressed within the thrombus and the aneurysm wall. NGAL can bind to metalloproteinase- 9 (MMP-9) and inhibit its degradation,thereby preserving enzymatic activity. Biopsies were obtained from thrombus- free and thrombus-covered aneurysm wall and the intraluminal thrombus from patients undergoing elective surgery for AAA. Immunohistochemistry and real-time PCR were used to study NGAL and MMP-9 expression. Immunoprecipitation, gel zymography,Western blot and ELISA were used to detect and quantify NGAL/MMP-9 complexes. NGAL was detected in the thrombus, the interface between the thrombus and the underlying wall and in the wall itself.Double staining showed that neutrophils are the major source of NGAL expression. Immunoprecipitation of MMP-9 with antibody against NGAL showed that complexes of NGAL and active MMP-9 were present in thrombus, the interface fluid and the aneurysm wall.Western blot analyses using non-reducing conditions and gel zymography demonstrated that high-molecular-weight complexes of NGAL/MMP-9 were present within the different regions.The concentration of the NGAL/MMP-9 complex was highest in the luminal part of the thrombus. In conclusion, NGAL in complex with activated MMP-9 is present in AAA wall and thrombus. Neutrophil-derived NGAL could enhance the proteolytic activity associated with AAA, but the importance of this mechanism for aneurysm growth remains to be shown.
Keywords: Abdominal aortic aneurysm; NGAL; matrix metalloproteinases-9; thrombus